The optimal timing for intervention in patients with ST-segment elevation myocardial infarction and multivessel disease: a systematic review and meta-analysis - Chen, Yi; Li, Meng; Wu, Yanqing (Frontiers in Cardiovascular Medicine, 2024)
The optimal timing for nonculprit vascular reconstruction surgery in patients with STsegment elevation myocardial infarction (STEMI) and multivessel coronary disease (MVD) is still controversial. Our aim was to explore the optimal intervention time for percutaneous coronary intervention (PCI) in STEMI patients who underwent MVD.The PubMed/Medline, EMBASE, Cochrane Library, and ClinicalTrials.gov databases were searched from inception to January 1, 2024 for clinical studies comparing immediate multivessel PCI and staged multivessel PCI in patients with STEMI. The primary outcomes were death from any cause, cardiovascular death, noncardiac death, myocardial infarction (MI) and unplanned ischemia-driven revascularization. The secondary outcomes were ischemic stroke, stent thrombosis, renal dysfunction and major bleeding. The risk ratios (RRs) and odds ratios (ORs) were calculated with fixed-effects models and random-effects models, and 95% confidence intervals (CIs) were calculated.Findings: Five randomized trials with 2782 patients and six prospective observational studies with 3131 patients were selected for inclusion in this meta-analysis. The staged PCI group had significantly lower pooled RRs for myocardial infarction (0.43, 95% CI=0.27-0.67; P = 0.0002) and unplanned ischemia-driven revascularization (0.57, 95% CI=0.41-0.78; P = 0.0004). There were no significant differences in any cause of death, cardiovascular cause of death, or noncardiac cause of death. However, the results of prospective observational studies in the real world indicated that the staged PCI group had significantly lower pooled ORs for all-cause mortality (2.30, 95% CI = 1.22-4.34; P = 0.01), cardiovascular death (2.29, 95% CI = 1.10-4.77; P = 0.03), and noncardiovascular death (3.46, 95% CI = 1.40-8.56; P = 0.007).Implications: According to our randomized trial analysis, staged multivessel PCI significantly reduces the risk of myocardial infarction and unplanned ischemia-driven revascularization compared to immediate multivessel PCI. There was no significant difference between the two groups in terms of all-cause mortality, cardiovascular mortality, or noncardiovascular mortality risk.However, prospective non-randomized studies suggest there might be a benefit in mortality in the staged PCI group. Therefore, staged multivessel PCI may be the optimal PCI strategy for STEMI patients with MVD.